Post‐traumatic lymphedema treatment with superficial circumflex iliac artery perforator lymphatic free flap: A case report. Issue 4 (15th February 2019) - Pereira, Nicolás; Cámbara, Álvaro; Kufeke, Matías; Roa, Ricardo
Abstract : Post‐traumatic lymphedema is poorly understood. It is rarely considered in limb reconstruction decision‐making approach. We report a case of a 41‐year‐old female who presented with right upper extremity lymphedema after degloving injury and split thickness skin graft, successfully treated with a superficial circumflex iliac artery perforator (SCIP) free flap restoring the lymphatic drainage. Right upper extremity had an excess of 258.7 mL or an excess volume of 27.86% compared to the healthy contralateral limb. A SCIP free flap including lymphatic vessels (SCIP‐L) was performed to replace the skin graft in order to restore the lymphatic flow. Flap size was 19 × 8 cm and pedicle length was 4 cm. No lymph nodes were included and no lymphatic or lymphovenous anastomoses were performed. The surgery was uneventful, and there were no postoperative complications. Fourteen days after free tissue transfer, lymphedema showed clear improvement. At a 4‐month follow‐up, 55.6% reduction of excess volume was obtained. Indocyanine green lymphography performed at that time showed a restitution of lymph flow through the flap. Lymphedema improvements persisted at a 6‐month follow‐up. A successful treatment of post‐traumatic lymphedema can be performed by using the SCIP‐L free flap for soft tissue reconstruction of critical lymphatic drainage areas.